Epidemiological and cytological aspects of the cervix in women from the Diourbel region (Senegal) cervical smear screening - Ndiade, Amadou; Thiam, Ibou; Diallo, Abdou Karim; Diatta, Ange Lucien; Senghor, Fabrice; Faye, Oumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Objectives of the study were to record the results of uterine cervical smear tests of women in the Diourbel region to compare epidemiological data with the results of uterine cervical smear tests. Methods: This was a retrospective study of 201 satisfactory cervical smears performed in the period from 01 December 2018 to 01 December 2019 at the laboratory of the regional hospital Henrich Lubcke of Diourbel. All women with a satisfactory smear were included in our study, so we classified patients according to age and parity. Results: The mean age of the patients was 38.41 years with a standard deviation of 11.51 years. The extremes were 15 and 64 years. The age group (30-40 years) was in the majority at 32.34%. Multiparous patients were in the majority, accounting for 43.28%. The cervix was macroscopically healthy in 61.19% of patients and inflammatory in 12.94%. There was 18.41% low-grade squamous intraepithelial lesion (LSIL), high-grade squamous intraepithelial lesion (HSIL) accounted for 1% of smears. A statistically significant relationship existed between parity and smear result with p˂0.01. Conclusions: Cervical cancer is one of the most fatal cancers in women and the smear remains the safest and most effective means of prevention.